Evaluation and optimization of PEM Fuel Cell-based CCHP system based on Modified Mayfly Optimization Algorithm. (November 2021) - Wei, Donghui; Ji, Jinghong; Fang, Junlong; Yousefi, Nasser
Abstract: In the present study, an optimal Proton-Exchange Membrane Fuel Cell-based includes Cooling, Heating, and Power system has been proposed to cover the required energy of the households for cooling, heating and electricity. The system is optimized by a modified version of the Mayfly Optimization (MMFO) algorithm to recover and develop the efficiency of the CCHP system. The innovation is the application of the proposed MMFO algorithm to provide the optimal configuration of the CCHP system in terms of environmentally and economically. the CCHP system is then simulated and its results are compared with NSGA-II from the literature, and also the original MFO method to indicate the method efficiency. The results indicate that the proposed optimal CCHP system offers good results and prominence toward the compared algorithms in both terms of environmental and efficiency.